Microglia–Astrocyte Communication via C1q Contributes to Orofacial Neuropathic Pain Associated with Infraorbital Nerve Injury - Asano, Sayaka (Int J Mol Sci, 2020)
Trigeminal nerve injury causes a distinct time window of glial activation in the trigeminal spinal subnucleus caudalis (Vc), which are involved in the initiation and maintenance phases of orofacial neuropathic pain. Microglia-derived factors enable the activation of astrocytes. The complement component C1q, which promotes the activation of astrocytes, is known to be synthesized in microglia. However, it is unclear whether microglia–astrocyte communication via C1q is involved in orofacial neuropathic pain. Here, we analyzed microglia-astrocyte communication in a rat model with infraorbital nerve injury (IONI). The orofacial mechanical hypersensitivity induced by IONI was significantly attenuated by preemptive treatment with minocycline. Immunohistochemical analyses revealed that minocycline inhibited the increase in c-Fos immune-reactive (IR) cells and the fluorescence intensity of both Iba1 and glial fibrillary acidic protein (GFAP) in the Vc following IONI. Intracisternal administration of C1q caused orofacial mechanical hypersensitivity and an increase in the number of c-Fos-IR cells and fluorescence intensity of GFAP. C1q-induced orofacial mechanical hypersensitivity was completely abrogated by intracisternal administration of fluorocitrate. The present findings suggest that the enhancement in the excitability of Vc nociceptive neurons is produced by astrocytic activation via the signaling of C1q released from activated microglia in the Vc following IONI, resulting in persistent orofacial neuropathic pain.